Analisis Faktor Penyebab Banyaknya Sisa Material Cable dari Produksi Kapal X pada Pt. XYZ Menggunakan Metode New Seven Tools - Muhammad Hafiz Aziz; Yekti Condro Winursito (Jurnal Teknik Mesin, Industri, Elektro dan Informatika, 2024)
XYZ is a company operating in the largest shipping manufacturing industry in Indonesia. Apart from that, PT. XYZ also accepts ship maintenance such as overhaul and ship repair work. PT. XYZ launched a ship created by the nation's children, named Ship X. This ship has a big impact because this ship can help provide medical assistance in underdeveloped, remote and frontier areas. However, in the production process of this ship there are still some remaining materials which can be said to be a lot. One of them is cable. To overcome this problem, analysis is needed to find out what factors can influence it and proposals that can solve the problem. In this research, the New Seven Tools analysis method was used. Based on the results of the analysis using the new seven tools method, it was found that the factors causing the large amount of leftover cable material were the lack of accuracy of both staff and field workers in determining material requirements and material processing. So that improvement evaluations can be carried out by determining the design and need for fixed materials in accordance with applicable SOPs, increasing worker productivity, and optimizing material processing during the production process.